A CMOS analog front-end IC for portable EEG/ECG monitoring applications - Ng, K. A. (2009)
A new digital programmable CMOS analog front-end (AFE) IC for measuring electroencephalograph or electrocardiogram signals in a portable instrumentation design approach is presented. This includes a new high-performance rail-to-rail instrumentation amplifier (IA) dedicated to the low-power AFE IC. The measurement results have shown that the proposed biomedical AFE IC, with a die size of 4.81 mm2, achieves a maximum stable ac gain of 10 000 V/V, input-referred noise of 0.86 Vrms (0.3 Hz–150 Hz), common-mode rejection ratio of at least 115 dB (0–1 kHz), input-referred dc offset of less than 60 V, input common mode range from 1 5 V to 1.3 V, and current drain of 485 µA (excluding the power dissipation of external clock